From the History of the Spread of Western Educational Ideas in Georgia (early 20th century) - Loria, Giorgi (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
At the beginning of the 20th century, Georgian magazines and news-papers widely covered the current situation in the country's educational life, information on teaching and upbringing, school textbooks, the training of professional teachers, and other issues. At this time, the views of Hermann Weimer, Jean-Jacques Rousseau, Otto Lippmann, Friedrich Nietzsche, Herbert Spencer, William James, Heinrich Pestalozzi, Jan Amos Comenius, Cornelius Gurlitt, and others were published, as well as various letters about the organization of European and American school life, learning methods, teachers' professional associations, and problems existing in schools and their overcoming. Two factors contributed to the spread of Western educational ideas in Georgia: 1. At the turn of the 19th and 20th centuries, European educational views, which were intensively spread in democratic circles in Russia, also influenced Georgia; 2. After returning to their homeland, young people educated in Europe actively participated in the renewal of the Georgian education system and, with the help of numerous magazines and newspapers, tried to share advanced European experience. One of the first professional educational journals in Georgia, „Education“, was distinguished by its publications about Western educational life, the founder, publisher and editor of which was the famous public figure, educator and public teacher Luarsab Botsvadze. Based on the historical-comparative research method used by us, the work analyzes the activities of the journal „Education“ in the history of the spread of Western educational views. The results of the research showed that a large part of the publications were translated by Luarsab Botsvadze and his associates and were oriented towards the needs of Georgian educational life, the need to share the experience of advanced European school life. The research confirmed the stated main goals and objectives, priority topics and conceptual educational visions of the journal.